Effect of exercise detraining in cognitive functions of older adults: A systematic review - Ferreira, Leonardo Gonçalves; Krajnak, Jakub; Paludo, Ana Carolina; Gimunova, Marta; Svobodová, Lenka; Stein, Angelica Miki (Archives of gerontology and geriatrics, 2024)
OBJECTIVE: Provide a synthesis of the current literature about the effects of detraining on cognitive functions in older adults. METHODS: The PICOS acronym strategy was performed in PubMed/MEDLINE, Web of Science, Cochrane Library and PsycINFO database. The Preferred Reporting Items for Systematic Review and Meta-Analyses statement had been followed in the present study, in which the search was conducted on October 2023. The study selection consisted in original articles including older adults, detraining after training exercise period, use of tests or scales to measure cognitive function. The Downs and Black checklist had been used to assess the studies quality. Sample characteristics, type of previous training, detraining period, cognitive functions measurements and main results were extracted by 2 investigators. RESULTS: From 1927 studies, 12 studies were included, being 11 studies identified via systematic research, and 1 study by citation search. Older adults, ranged from 60 to 87 years old, were assessed after detraining. The cognitive functions most evaluated were global cognition and executive functions. One study evaluated both cognitive outcome and cerebral blood flow. Most of the studies demonstrated a decline in the cognitive function after detraining. CONCLUSION: Exercise detraining period, ranging from 10 days to 16 weeks, can effect negatively the cognitive function in older adults.
Keywords: kognitivní dysfunkce; Cognition; kognice; lidé středního věku; Executive Function; lidé; senioři nad 80 let; senioři; Cognitive Dysfunction; cvičení; exekutivní funkce; Exercise; Aged; Middle Aged; Aged, 80 and over; Humans